The Correlation between Facial Nerve Grading System 2.0 and the Sunnybrook Facial Grading System in Subjects with Facial Palsy: A Cross-Sectional Study - Abbas Ali Pourmomeny; Elham Pourali; Amir Heydari (Vesnu Publications, 2019)
Introduction: Over many years, several methods have been developed to evaluate the facial nerve palsy. Among them, Sunnybrook Facial Grading System (SFGS) and modified House-Brickmanne, known as Facial Nerve Grading System 2.0 (FNGS 2.0), grading systems have been the most favored methods to evaluate facial nerve health between therapists and researchers. The aim of this study was to compare these two evaluation approaches. Materials and Methods: In the present cross-sectional study, the videotapes for nineteen subjects diagnosed with facial nerve palsy were recorded before and after treatment. Then, the videotapes were evaluated using the SFGS and FNGS 2.0 scales by three specialists separately. The inter-rater agreement was reported using Intraclass correlation coefficient (ICC) scores. The correlation between the two evaluation approaches was determined using Spearman's coefficient of correlation. Results: The ICC score for scoring by the specialists was 0.969 for SFGS and 0.904 for FNG 2.0. The FNG 2.0 and SFGS inter-system agreement reported as 0.848 (P < 0.01). The coefficient was higher before treatment (0.961), and decreased after treatment (0.777). Conclusion: Although the correlation between two systems was acceptable, the SFGS system was more sensitive than FNG 2.0.